Coast lines how mapmakers frame the world and chart environmental change - Monmonier, Mark S. (University of Chicago Press, 2008)
Covering shifting landscapes, cartographic technology, and climate change, this book reveals that coastlines are as much a set of ideas, assumptions, and societal beliefs as they are solid black lines on maps. It charts the historical progression from offshore sketches to satellite images